Revalidation of the genus Ectrepopterus Fowler (Teleostei: Characiformes), with the redescription of its type species, E. uruguayensis - Malabarba, Luiz R.; Bertaco, Vinicius A.; Carvalho, Fernando R.; Litz, Thomas O. (Zootaxa, 2012)
Ectrepopterus uruguayensis Fowler 1943 is redescribed based on the holotype and new series of additional specimensfrom the río Uruguay, río Negro, and small coastal rivers in Uruguay draining to the río de La Plata. Previously proposedsynonyms of Ectrepopterus Fowler 1943 to Megalamphodus Eigenmann 1915 and Hyphessobrycon Durbin 1908 aretested and refuted. A new diagnosis is presented for the genus based on the following apomorphies: foramen in posteriorregion of metapterygoid forms an incomplete arch, bordered posteriorly by the hyomandibula; pectoral-fin rays bearinghooks; posterior margin of second infraorbital posteroventrally oblique and second infraorbital ventrally borderinganterior region of third infraorbital; fourth infraorbital more developed longitudinally than dorsoventrally; ascending process of premaxilla reaching just anterior end of nasal; and lateral line interrupted.